Decoding conscience: drawing inspiration from the ethical journey of Thomas More - Hernandez-Ojeda, Jaime (Moreana, 2024)
This article is dedicated to meticulously exploring the intricate facets of Thomas More's conscience, seeking insightful comparisons with the perspectives of his contemporaries. In the pursuit of a comprehensive understanding, the narrative carefully considers the profound teachings concerning synderesis and conscience, with a particular focus on highlighting the interplay between prudence and conscience as perceived by More. Furthermore, the analysis contrasts these foundational ideas with modern interpretations of the concept of conscience. Currently, concerns arise over the suppression of conscience, which can result in the dehumanization of society and present moral hazards. Equating conscience with superficial conviction is seen as a form of bondage, fostering reliance on prevailing opinions. Examining More's ethical journey proves valuable in comprehending the genuine significance of conscience. By delving into More's ethical dilemmas, we understand that objections raised by individuals stem not from whims but from deeply held convictions intricately linked to trut.